Peningkatan Kemampuan Kewirausahaan (Santripreuneu Rship) Melalui Budidaya Maggot Terintegrasi Peternakan Di Pondok Pesantren Alhikmah Bogor - Dino Rimantho; Gunawan Baharuddin; Agung Saputra (SULUH: Jurnal Abdimas, 2025)
Pondok Pesantren Qur’an Al-Hikmah in Bogor Regency faces two major issues: ineffective organic waste management and low interest in entrepreneurship among students and teachers. This program aims to enhance entrepreneurial understanding through training in Black Soldier Fly (BSF) Maggot cultivation integrated with chicken farming, catfish farming, and hydroponics. The training is designed to provide a comprehensive solution to the challenges faced, emphasizing waste management as a resource that can be processed into economically valuable products. The results of this program show that students and teachers experienced an increase in understanding and motivation for entrepreneurship after participating in the training. Additionally, the Islamic boarding school responded positively to the program's implementation, with many participants enthusiastically engaging in the training. The implication of this activity is the creation of opportunities for independent businesses based on BSF Maggot cultivation within the boarding school environment, which can enhance the economic independence of students and teachers after graduation.